Feasibility study for development of CitraLand Puri Serang area (Kayana District) - Georgius Pranayogi; Wirawan Endro Dwi Radianto (Institute of Computer Science (IOCS), 2023)
This feasibility study considers aspects of industrial structure and environment, market and marketing aspects, technical aspects, human resource aspects, and financial aspects. This study aims to see the feasibility of developing the CitraLand Puri Serang housing complex from the point of view of the Ciputra Group companies and partners (landowner) who have been working together since 2014 with the Joint Operation (Revenue Sharing) system. The method used is qualitative with observation, questionnaires and interviews with parties who are considered important as resource persons. The results of this study show the feasibility of developing this project for both parties, where the Ciputra Group companies get the maximum profit, and the partner companies benefit in a short period of time from the land developed and managed by the Ciputra Group